In Vivo MR Microneurography of the Tibial and Common Peroneal Nerves - Paolo F. Felisaz; Eric Y. Chang; Irene Carne; Stefano Montagna; Francesco Balducci; Giulia Maugeri; Anna Pichiecchio; Fabrizio Calliada; Maurizia Baldi; Stefano Bastianello (Radiology Research and Practice)
MR microneurography is a noninvasive technique that provides visualization of the microanatomy of peripheral nerves, otherwise available only with histopathology. The objective of this study was to present a protocol to visualize the microstructure of peripheral nerves in vivo, using a 3T MRI scanner with a clinical set of coils and sequences. The tibial and the common peroneal nerves of healthy volunteers were imaged above the medial malleolus and at the level of the fibular head, respectively. The acquired images provided details about the internal structure of peripheral nerves, with visualization of the fascicles, the interfascicular fat, the epineurium, and the perineurium. MR microneurography can be performed in a clinical setting with acceptable imaging times and can be a potentially powerful tool that complements standard MR neurography.